Effects of ballistic and maximal resistance training on throwing velocity in well-trained female handball players - Sundan, J. (Nord-Trøndelag University College, Faculty of Teacher Education Levanger, 2009)
The aim of this study was to investigate the effects of ballistic and maximal general resistance training upon throwing velocity. Fifteen well-trained female handball players (18.5±1.3 yr) volunteered to participate in the study. A nine week pre- to post design was chosen, and subjects were matched pair-wise into two groups based on pretest throwing velocity performance: maximal training group (MTG, n = 7) and ballistic training group (BTG, n = 8). Standing and three-step run- in throwing velocity was tested before and after a seven week training intervention period. In addition, subjects were tested for: (1)maximal strength in bench press (1RM), (2) peak power, peak velocity, time to peak power and time to peak velocity in the bench throw (40% of 1RM). The major finding of this study was that the three-step run-in throwing velocity significantly decreased for both groups from pre- to posttest (BTG: P = 0.005, MTG: P = 0.037), whereas a minor decrease were found for the standing throw. Ano ther finding in this study was that MTG increased their 1RM bench press performance significantly as compared to the BTG (P = 0.005). Both groups increased their peak power (BTG: P = 0.009, MTG: P = 0.007) and peak velocity (BTG: P = 0.001, MTG: P = 0.014) significantly, but no significant difference was observed between groups. In conclusion, both groups impaired their throwing velocity performance. Results of this study may indicate that ballistic resistance training is not superior to maximal resistance training for increasing throwing velocity.